Resous chaque equation si desous A)-2(2x-4)=6x-(-3+x) B)4x-2+(5x-1=-3(7-x C)((x+5)÷2)-((2x-7)÷5=2+3x÷10 Cordialement
Mathématiques
totomato744
Question
Resous chaque equation si desous
A)-2(2x-4)=6x-(-3+x)
B)4x-2+(5x-1=-3(7-x
C)((x+5)÷2)-((2x-7)÷5=2+3x÷10
Cordialement
A)-2(2x-4)=6x-(-3+x)
B)4x-2+(5x-1=-3(7-x
C)((x+5)÷2)-((2x-7)÷5=2+3x÷10
Cordialement
2 Réponse
-
1. Réponse maudmarine
Bonjour,
A)-2(2x-4)=6x-(-3+x)
- 4x + 8 = 6x + 3 - x
- 4x - 6x + x = 3 - 8
- 9x = - 5
x = 5/9
B)4x-2+(5x-1=-3(7-x )
4x - 2 + 5x - 1 = - 21 + 3x
4x + 5x - 3x = - 21 + 2 + 1
6x = - 18
x = - 18/6
x = - 3
C)((x+5)/2)-((2x-7)/5=2+3x/10
((5x + 25) / 10) - ((4x - 14) / 10) = 20/10 + 3x/10
5x + 25 - 4x + 14 = 20 + 3x
5x - 4x - 3x = 20 - 25 - 14
- 2x = - 19
x = 19/2
x = 9,5
-
2. Réponse louisefra64
Réponse :
slt !
a) -2 (2x-4)= 6x -(-3+x)
-4x + 8 = 6x + 3 + x
-4x + 8 - 8 = 7x + 3 -8
-4x = 7x -5
-4x -7x = 7x -5 -7x
-11x = -5
-11x : -11 = -5 : -11
x = [tex]\frac{-5}{-11}[/tex]